Integrasi Dan Optimalisasi Alur Kerja Pengembangan Website Lokal Menggunakan Aplikasi Xampp Tools Berbasis Electron - Lukman Muludin; Nur Aisyah; Tria Suwanita; Rifqah Alfiyah Zahra; Ega Stinka (CV. Multi Kreasi Media, 2025)
This research discusses the development and implementation of the XAMPP Tools application as an integrated solution to improve efficiency in XAMPP-based web development workflows. Although XAMPP has been widely used as a local platform in web development, users often encounter difficulties in terms of project management and server configuration. The XAMPP Tools application built using the Electron framework presents a graphical interface that facilitates the process of creating projects, setting up servers, and handling common problems that often occur with XAMPP. The research approach includes identifying user needs, designing application systems, implementing key features, and evaluating application performance. The results show that the use of XAMPP Tools can speed up the project creation process by 75%, simplify server management, and significantly reduce the duration of MySQL problem solving. These findings are an important contribution to providing tools for more efficient local web development, by increasing productivity and lowering technical barriers for developers.